Kajian Konfirmatif Dampak Disiplin Siswa dan Tingkat Pendidikan Orang Tua pada Peningkatan Prestasi Belajar Siswa - Wahyu Dwi Lestari; Siami (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
Student discipline and parental education have become the object of study because of their impact on student achievement. The purpose of the study was to confirm the theory and the results of previous studies which stated that there was a relationship between discipline and parental education level on student achievement. The subjects studied were students from SD Sunan Giri Ngebruk Sumberpucung Malang, with the unit of observation being these students. Learning achievement is limited to Islamic Religious Education subjects. The research uses a quantitative approach, where data is obtained through a survey using a questionnaire. A total of 85 respondents' answers were processed using regression analysis. The results show that there is an influence between discipline, and the level of parental education on student achievement. The research has implications for the importance of disciplined learning behavior in children and the importance of highly educated parents in order to encourage children to be more enthusiastic about learning in order to improve their learning achievement.